IC 9400 Analyses Of Natural Gases, 1993 - Stella Sigler (The National Institute for Occupational Safety and Health (NIOSH), 1994)
This publication contains analyses and related source data for 153 natural gas samples from 16 States. Of the total samples, 149 were collected during calendar year 1993. The remainder were collected earlier, but releases granting permission to publish were not received until 1993. None of the analyses have been previously published in annual reports. All samples were obtained and analyzed as part of U.S. Department of the Interior, U.S. Bureau of Mines investigations of the occurrences of helium in natural gases of countries with free market economies. This survey has been conducted since 1917. The analyses published herein were made by mass spectrometer and chromatograph.